2021
DOI: 10.3390/jpm11030174
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Brain Microstructure and Network Alterations in Depressive Patients with Suicide Attempts Using Generalized Q-Sampling MRI

Abstract: Depressive disorder is one of the leading causes of disability worldwide, with a high prevalence and chronic course. Depressive disorder carries an increased risk of suicide. Alterations in brain structure and networks may play an important role in suicidality among depressed patients. Diffusion magnetic resonance imaging (MRI) is a noninvasive method to map white-matter fiber orientations and provide quantitative parameters. This study investigated the neurological structural differences and network alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In addition, SA showed reduced activation in the OFC for the contrast between disadvantageous and advantageous choices (Jollant et al, 2010). Other authors (Kaschka & Rujescu, 2016;Zhang et al, 2019) have reported in SA structural alterations in CC and deficits in emotion regulation and impulse control (Cyprien et al, 2011;Emsell et al, 2013;Gan et al, 2016;Matsuo et al, 2010) It has been suggested that WM abnormalities also play a critical role in the pathogenesis of psychiatric disorders (Chen et al, 2021). DTI studies revealed disrupted connectivity within the DMN accompanying mood disorders (Hamilton et al, 2015) and rumination (Berman et al, 2011;Lois & Wessa, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, SA showed reduced activation in the OFC for the contrast between disadvantageous and advantageous choices (Jollant et al, 2010). Other authors (Kaschka & Rujescu, 2016;Zhang et al, 2019) have reported in SA structural alterations in CC and deficits in emotion regulation and impulse control (Cyprien et al, 2011;Emsell et al, 2013;Gan et al, 2016;Matsuo et al, 2010) It has been suggested that WM abnormalities also play a critical role in the pathogenesis of psychiatric disorders (Chen et al, 2021). DTI studies revealed disrupted connectivity within the DMN accompanying mood disorders (Hamilton et al, 2015) and rumination (Berman et al, 2011;Lois & Wessa, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that WM abnormalities also play a critical role in the pathogenesis of psychiatric disorders (Chen et al., 2021 ). DTI studies revealed disrupted connectivity within the DMN accompanying mood disorders (Hamilton et al., 2015 ) and rumination (Berman et al., 2011 ; Lois & Wessa, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study by Chen et al evaluated white-matter integrity (generalized fractional anisotropy) and white-matter compactness (normalized quantitative anisotropy) among depressive patients with and without past suicide attempts ( 96 ). On a voxel-based (region of interest) analysis, participants with past suicide attempts had significantly lower white matter compactness and integrity in the corpus callosum, cingulate gyrus, and caudate than both the depressed non-attempt and the healthy control groups, with differences between the attempt group and healthy control group reaching statistical significance ( 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study used DTI for research on white matter integrity to evaluate the value of FA in patients with suicidal ideation. DTI is not able to distinguish branching or crossing bers [40]. To address this limitation, we turned to diffusion kurtosis imaging (DKI), which offers additional metrics closely related to tissue microstructure.…”
Section: Discussionmentioning
confidence: 99%